Pengaruh Tekanan Pekerjaan dan Stres Pekerjaan terhadap Evaluasi Kinerja - Logahan, Jerry M. (Bina Nusantara University, 2009)
The lawyer profession at this time has become the public spotlight due to their role in upholding justice and defending the oppressed. This noble work requires reliable performance. Therefore, performance evaluation of lawyers needs to be considered. Factors that affect the performance evaluation of lawyers should also be investigated further. The purpose of this study is to see the correlation of job stress and pressure of work on performance evaluation of the lawyers, especially in corporate law firm